PENGARUH PROFITABILITAS, KUALITAS AUDIT, INDEPENDENSI AUDITOR, UKURAN PERUSAHAAN, DAN LEVERAGE TERHADAP MANAJEMEN LABA - Ayu Winda Pratiwi; Patricia Diana (Sekolah Tinggi Ilmu Ekonomi Wiyatamandala, 2018)
The objective of this research is to obtain empirical evidence about the effect of profitability, audit quality, auditor independency, firm size, and leverage either individually or simultaneously toward earnings management. Dependent variable of this research was earnings management measured by discretionary accruals with modified jones model. Earnings management is an action taken by management to determine current reported earnings based on judgment that may reduce the credibility of the financial statements, so the information presented can mislead decision-makers. Independent variables were profitability, audit quality, auditor independency, firm size, and leverage. The object in this research was manufacturing companies listed in Indonesia Stock Exchange (IDX) for period 2013 until 2015. The samples in this research were 103 companies listed on IDX in 2013 – 2015 were selected by using purposive sampling method. Secondary data used in this research was analyzed by using multiple regression method. The results of this research were: (1) Profitability had significant effects on earnings management, (2) Audit quality had no significant effects on earnings management, (3) Auditor independency had no significant effects on earnings management, (4) Firm size had no significant effects on earnings management, and (5) Leverage had no significant effects on earnings management.